2015
DOI: 10.1016/j.tiv.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of inositol hexaphosphate and its Ni(II) complex on human acute leukemia Jurkat T cells

Abstract: Inositol hexaphosphate (InsP6) is present in cereals, legumes, nuts and seed oils and is biologically active against some tumor and cancer cells. Herein, this study aimed at evaluating the cellular toxicity, antiproliferative activity and effects on cell cycle progression of free InsP6 and InsP6-Ni(II) of leukemic T (Jurkat) and normal human cells. Treatments with InsP6 at concentrations between 1.0 and 4.0mM significantly decreased the viability of Jurkat cells, but showed no cytotoxic effect on normal human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…49 reported that PA extracted from rice bran was not toxic up to 6 mM for 72 h in untransformed cultures of 3T3 cells, yielding < 10% of dead cells 49 , Similar results were reported by de Lima et al . 50 who did not observe PA cytotoxicity at 4.0 mM for 48 h in lymphocytes isolated from healthy human donors. In this work, cytotoxicity (IC 50 ) of PA and derivatives was tested in MSCs cultures using a standardized Alamar Blue assay.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…49 reported that PA extracted from rice bran was not toxic up to 6 mM for 72 h in untransformed cultures of 3T3 cells, yielding < 10% of dead cells 49 , Similar results were reported by de Lima et al . 50 who did not observe PA cytotoxicity at 4.0 mM for 48 h in lymphocytes isolated from healthy human donors. In this work, cytotoxicity (IC 50 ) of PA and derivatives was tested in MSCs cultures using a standardized Alamar Blue assay.…”
Section: Resultsmentioning
confidence: 93%
“…Biological properties of PA have been widely studied in different in vitro and in vivo models 2,4750 , Using healthy cells, Norhaizan et al . 49 reported that PA extracted from rice bran was not toxic up to 6 mM for 72 h in untransformed cultures of 3T3 cells, yielding < 10% of dead cells 49 , Similar results were reported by de Lima et al .…”
Section: Resultsmentioning
confidence: 99%
“…This compound has been employed in growth inhibition assays of human tumor cell lines (De Lima et al, 2015), as a protective agent in fishes with copper exposure (Jiang et al, 2014), as indicator during cellular apoptosis (Agarwal et al, 2010). Other compound: Maltose (0.02%) is a disaccharide that it has too many applications.…”
Section: Resultsmentioning
confidence: 99%
“…Cadmium can induce a delay in the transition between the G1 and S phases of the cell cycle, and slows progression through the S phase (28). Nickel (II) modulates cellular responses through effectors involved in G2/M arrest and apoptosis regulatory pathways (32,33). Rodríguez-Sastre et al (34) evaluated the capability of a mixture of 2 µM NaAsO 2 , 2 µM CdCl 2 and 5 µM Pb(C 2 H 3 O 2 ) 2 •3H 2 O at relevant epidemiological concentrations to induce cell transformation processes.…”
Section: Discussionmentioning
confidence: 99%